Miss Peregrine's: Library Of Souls - Book 3 - Riggs, Ransom; Heyborne, Kirby ([Ashland, Oregon] : Blackstone Audio, Inc., 2015)
Time is running out for the Peculiar Children. With a dangerous madman on the loose and their beloved Miss Peregrine still in danger, Jacob Portman and Emma Bloom are forced to stage the most daring of rescue missions. They'll travel through a war-torn landscape, meet new allies, and face greater dangers than ever.
Keywords: Orphanages -- Juvenile fiction; Rescues -- Juvenile fiction; Abnormalities, Human -- Juvenile fiction; Time travel -- Juvenile fiction; Teenagers -- Juvenile fiction; Audiobooks; Orphanages -- Fiction; Rescues -- Fiction; Time travel -- Fiction; Abnormalities, Human -- Fiction; Teenagers -- Fiction; Orphanages; Rescues; England -- Juvenile fiction; Children's audiobooks; Children's audiobooks; Fiction; Juvenile works; Paranormal fiction